REGIONAL MEDIATION ROLE AND IMPORTANCE IN THE SHANGHAI COOPERATION ORGANIZATION OF UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
Analyzes the activities of the Shanghai Cooperation Organization, the institutional legal basis of its organization, the participation of Uzbekistan in the framework of the organization, its initiatives, and the prospects expected from it. Scientific research of the SCO and prediction of its future are gaining urgent importance in today's rapidly changing system of international relations. Factors such as expansion of the organization's geopolitical map due to the increase in the number of members, as well as a high level of economic potential, open wide opportunities for the developing countries of the SCO. From this point of view, Uzbekistan, which is considered a full member, is promoting many initiatives and gaining opportunities to make the most of such opportunities. depend on the effectiveness of such initiatives and proposals. During the analysis, we discuss Uzbekistan's participation in the organization, its economic goals and geopolitical strategies.